Analysis of the Effect of Taxpayer Knowledge and Awareness on Taxpayer Compliance at XYZ Consulting - Aulia, Dinda; Utama, Ida Bagus Made; Masari, Ni Made Galih (PT FORMOSA CENDEKIA GLOBAL, 2024)
Given that taxes are the main source of state treasury funding, it is difficult to implement state initiatives such as national development without state treasury funding from the taxation sector. At XYZ Consulting, the researcher's objective is to evaluate and assess how compliance awareness in filing taxes is affected by taxation knowledge. Descriptive methods and quantitative research techniques were combined in this study. This research involves individuals or entities from XYZ Consulting who are taxpayers. To determine the research sample, 54 responses were collected using the Slovin formula calculation method. According to XYZ Consulting, the Study findings show that taxpayer compliance is significantly influenced by taxpayer awareness and knowledge and both factors significantly improve compliance at the same time.